Visualização cartográfica da acessibilidade geográfica aos postos de saude da região rural de Registro (SP) - Ricardo Vicente Ferreira; Jorge Da Graça Raffo (Confins)
Mapping of road network and modeling of spatial data can be used to identify restrictions of movement through vehicle of transportation. Through such mapping is possible an overview of the accessibility of rural populations to health care services. In this study, a cartography and Geographic Information Systems (GIS) are presented to describe the accessibility of rural people to health care services in the region of Registro (SP). The study on geographical accessibility is of critical importance on people's health care rights. The idea of accessibility by general population to health care can be seen from the perspective of a geographical potential. The specialized literature addresses this issue as potential physical accessibility. Under this proposal, the evaluation of the accessibility of a region does not require the analysis of empirical data, once part of the idea that every resident in the region of health administration is a potential user of the medical and hospital services. Therefore, measurement on geographical accessibility can be analyzed according to the position of each residents of an area regarding provider location. The present paper uses the concept of cartography of synthesis as base for construction of models in Spatial Analysis GIS-based and displays maps of potential physical accessibility in region of Registro (SP). The thematic representations of the region show three aspects: (i) the geometry of the rural road network, (ii) geographic mobility, and (iii) geographic accessibility to health services through road network.